UNDERSTANDING THE CHILD’S MIND THROUGH LITERATURE: A PSYCHOLOGICAL STUDY IN PINKALICIOUS INNER CONFLICT BY VICTORIA KANN AND ELIZABETH KANN - Anjelika Anjelika; Resneri Daulay (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
The purpose of this study is to analyze the internal conflict experienced by the main character in the children's literature work “Pinkalicious” by Victoria Kann and Elizabeth Kann. Furthermore, this study also analyzes the self-defense mechanisms, specifically denial and rationalization attitudes, of the main character, Pinkalicious, when facing problems through the lens of Sigmund Freud's psychological personality theory. Then, the research method employed in this study is a descriptive qualitative approach. The data obtained in this study came from the short story “Pinkalicious” by Victoria Kann and Elizabeth Kann, in the form of quotations and dialogues, which reveal the personality structure of the main character, Pinkalicious. Regarding the results of this study, the Id and Ego structures control the Pinkalicious character's attitude in everyday life. However, the superego can reduce the attitudes of the id and ego, which makes Pinkalicious a little loosened. As a result, the form of self-defense mechanisms carried out by the main character, Pinkalicious, only focuses on denial and rationalization. Therefore, this greatly influences the personality of the main character, Pinkalicious, in terms of decision-making.